Police Strategy in Preventing Cases of Motor Gangs in Sukabumi City - Siti Hasni Hutami; Dine Meigawati; Rizki Hegia Sampurna (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Motorcycle gangs in Sukabumi City often cause unrest in the community because they can occur anytime and anywhere. In Sukabumi City itself, the intensity of the existence of motorcycle gangs is growing. Thus, the Sukabumi City police made a strategy on how to prevent motorcycle gangs that are troubling in Sukabumi City. Thus, to find out and measure how the strategy is carried out, this research uses Mulgan (2009) with 4 Strategy indicators namely Purpose, Environment, Araha, and Action. The research method used in this research is descriptive method with a leatherative approach. The purpose of this research is to find out the extent to which this strategy is running and the impact produced by this strategy. The results of this study show that the collaboration run by Sukabumi Police has not been running optimally because it has not fulfilled the 4 indicators of Mulgan (2009) because in the Environmental Indicator there are still obstacles from family and friendship so it needs to be reviewed again.